Microbial transformation of primaquine by Candida tropicalis. - Clark, A M (1984)
The microbial metabolism of primaquine, a 6-methoxy-8-aminoquinoline antimalarial agent, was investigated. The yeast Candida tropicalis was found to convert primaquine to the previously reported N-acetylated derivative. On continued incubation of C. tropicalis in the presence of the N-acetylated derivative, a minor dimeric metabolite was formed. The proposed structure of the metabolite was based primarily on the analysis of its spectroscopic properties (1H and 13C nuclear magnetic resonance spectra and field-desorption mass spectrum). The structure of the metabolite was proven by direct comparison with an authentic sample of the minor dimeric metabolite prepared by treatment of the N-acetylated derivative with formaldehyde in the presence of formic acid in methanol.